Addressing Mental Health Needs in Public Health Management: Bridging Gaps in Services and Support - Sachin Ayarekar (International Journal of Medical Toxicology and Legal Medicine, 2024)
Mental health issues represent a significant public health challenge globally, yet there remains a considerable gap in addressing these needs effectively within public health management systems. This paper explores the various dimensions of mental health within the context of public health management, focusing on identifying existing gaps in services and support. Drawing upon a comprehensive review of literature, this paper highlights the multifaceted nature of mental health challenges, including stigma, limited access to care, insufficient resources, and disparities in service provision. It examines the roles of different stakeholders, such as governments, healthcare providers, community organizations, and individuals, in addressing mental health needs. Moreover, this paper discusses potential strategies and interventions to bridge the existing gaps, including integrating mental health services into primary care, leveraging technology for remote interventions, promoting mental health literacy, and strengthening community-based support systems. By addressing these challenges and implementing effective interventions, public health management can better respond to the mental health needs of populations, ultimately contributing to improved well-being and reduced burden of mental illness.